Immobilisation of Iron Porphyrin from an Equilibrium Solution with Diazonium‐Functionalised Axial Ligand: Dependence of Film Composition on Grafting Potential. Issue 16 (17th August 2021) - Wu, Ting; Brooksby, Paula A.; Fitchett, Christopher M.; Downard, Alison J.
Abstract: In dichloromethane solution, tetraphenylporphyrin iron (III) chloride (FeTPPCl) and 4‐(1 H ‐Imidazol‐1‐yl)aniline (Im‐Ph‐NH2 ) exist in equilibrium with axially‐coordinated [FeTPP(Im‐Ph‐NH2 )n ] + (n=1 and 2). After in situ diazotisation of Im‐Ph‐NH2, electroreduction of the diazonium ion leads to deposition of a film incorporating [FeTPP(Im‐Ph)2 ] + and uncoordinated Im‐Ph. In the 1 : 1 FeTPPCl:Im‐Ph‐NH2 grafting solution used in this work, Im‐Ph‐NH2 is mostly uncoordinated. However, the formation constant for axially coordinated Fe(II)TPP is significantly greater than for Fe(III)TPP + . Consequently, the relative amounts of coordinated and uncoordinated Im‐Ph in the films depends on whether the grafting scans traverse the potential for reduction of FeTPPCl. In addition, redox grafting can occur based on the Fe(III)/(II) couple of solution‐ and film‐based porphyrin. Electrochemistry, atomic force microscopy and X‐ray photoelectron spectroscopy reveal that the relative amount of free and coordinated Im‐Ph, and concentration of [FeTPP(Im‐Ph)2 ] + in the films depend on the negative potential limit during grafting. Abstract : A simple method for immobilising metalloporphyrin employs a diazonium ion‐derivatised axial ligand. However, when there is an equilibrium between the axially‐coordinated and uncoordinated porphyrin, grafting deposits both free (uncoordinated) and axially‐coordinated ligand to the porphyrin. The relative amounts of uncoordinated and coordinated ligand depend on the grafting potential, thus complicating the control of film composition.